2009
DOI: 10.1002/art.24328
|View full text |Cite
|
Sign up to set email alerts
|

Familial associations of rheumatoid arthritis with autoimmune diseases and related conditions

Abstract: Objective. In the era of genome-wide association studies, familial risks are used to estimate disease heritability and the likelihood of candidate-gene identification. This study was undertaken to estimate associations of rheumatoid arthritis (RA) with any of 33 autoimmune diseases and related conditions among parents and offspring, singleton siblings, twins, and spouses.Methods. The Multigeneration Register in Sweden was used as a reliable source of information on Swedish families throughout the last century.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
143
4
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(167 citation statements)
references
References 35 publications
11
143
4
9
Order By: Relevance
“…No indication to that effect was observed, nor have twin studies found evidence of shared environmental effects. The SIR for twins of unknown zygosity was 21.88, which was clearly higher than that for multiple sclerosis (9.09) or rheumatoid arthritis (6.48), which we have recently assessed in this same population [32,46]. The calculated type 1 diabetes risk for 48 monozygotic twins (0.2% of all patients) was 32.33, which was clearly higher than predicted from additive genetic effects calculated from the SIR of singleton siblings (SIR 11.92, excess risks 11.92−1.00=10.92; calculated for monozygotic twins: 10.92×2=21.84, which when added to the background rate of 1.00 amounts to 22.84).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…No indication to that effect was observed, nor have twin studies found evidence of shared environmental effects. The SIR for twins of unknown zygosity was 21.88, which was clearly higher than that for multiple sclerosis (9.09) or rheumatoid arthritis (6.48), which we have recently assessed in this same population [32,46]. The calculated type 1 diabetes risk for 48 monozygotic twins (0.2% of all patients) was 32.33, which was clearly higher than predicted from additive genetic effects calculated from the SIR of singleton siblings (SIR 11.92, excess risks 11.92−1.00=10.92; calculated for monozygotic twins: 10.92×2=21.84, which when added to the background rate of 1.00 amounts to 22.84).…”
Section: Discussioncontrasting
confidence: 57%
“…This Register has been extensively used to study hospitalised diseases, including familial autoimmune diseases, through linkage to the Hospital Discharge Register [21,22,[29][30][31][32]. In the present article we studied familial risks for type 1 diabetes among parents and offspring, and singleton siblings and twins.…”
Section: Introductionmentioning
confidence: 99%
“…A child whose mother has RA has a 3-fold increased risk of developing that condition sometime in life, meaning that an estimated 3% of the offspring of women with RA will develop it themselves. However, these offspring are also more likely to develop other rheumatic diseases at any time in life, including a 1.5-2.5-fold increased risk for SLE, ankylosing spondylitis, scleroderma, Sjö gren's syndrome, or hypothyroidism (29).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of transmission of complex disease between spouses is cited as evidence against microbial agents playing a role in pathogenesis or at least as evidence that a shared environment later in life is not an important etiologic factor. Although we are unaware of any evidence beyond case reports of an increase in relative risk for the spouse of an individual with multiple sclerosis, a small but significant increase risk of rheumatoid arthritis has been observed (49). In an analysis of two cohorts living in Belgium and France, the frequency of Crohn's disease after marriage to an individual with this disease was significantly increased relative to what would be expected by chance alone given the population size studied (50).…”
Section: A Model Of Microbial Inheritancementioning
confidence: 95%